1983
DOI: 10.2135/cropsci1983.0011183x002300060020x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Seedling Root Length and Relative Root Weight in Cotton1

Abstract: A perennial problem in cotton, Gossypium hirsutum L., involves obtaining a vigorous, uniform stand when planted early. Strains that grow roots longer and higher in relative root weight (mg/mm length) than currently used cultivars when temperatures are cool may help alleviate this. Using the standard cotton, cool temperature (18°C) germination test we determined root lengths and relative root weights for 124 day‐neutral composite F3 strains. Variability among lines was significant for each seed and seedling par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…These results have close resemblances to gene components that control the expression of root dry weight and root surface area in common bean (Araujo et al, 2005). Also in cotton, the gene effects of root characteristics showed that additive and additive  additive gene effects account for about 50% of the variation in root length in one of the two crosses tested at seedling stage (Eissa et al, 1983).…”
Section: Discussionsupporting
confidence: 58%
“…These results have close resemblances to gene components that control the expression of root dry weight and root surface area in common bean (Araujo et al, 2005). Also in cotton, the gene effects of root characteristics showed that additive and additive  additive gene effects account for about 50% of the variation in root length in one of the two crosses tested at seedling stage (Eissa et al, 1983).…”
Section: Discussionsupporting
confidence: 58%
“…In other species, genetic variation for root/shoot ratio has also been commonly observed (Eissa et al, 1983; Downloaded by [Monash University Library] at 11:33 04 February 2015 Gabelman et al, 1986;Singh et al, 1988;McMichael and Quisenberry, 1991). For many species, narrow sense heritabilities for root/shoot ratio were high (hN > 0.5), e.g.…”
Section: Results and Discussion Comparison Of Cultivarsmentioning
confidence: 96%
“…Significant correlations between shoot and root dry weight of cultivars or genotypes within species have been commonly observed (Ali-Khan and Snoad, 1977;Monyo and Whittington, 1970;Salleh and Gritton, 1988;Singh et al 1988;Veronesi, 1990) but are not universal (Eissa et al, 1983;McMichael and Quisenberry, 1991). Highest correlations between root dry weight and either shoot dry weight, leaf number, or stolon length were recorded at low and intermediate P levels (40,120, and 200 mg P/kg soil) (Table 6a), levels at which responses to P were occurring (Figure 1).…”
Section: Relationship Between Root and Shoot Charactersmentioning
confidence: 99%
“…, Eissa et al. , Taylor , Cook , Ludlow and Muchow ). Physiological traits include leaf water content, carbon isotope discrimination (Leidi et al.…”
mentioning
confidence: 98%